Focus on Cardiologic Findings in 30 Children With PANS/PANDAS: An Italian Single-Center Observational Study - Murciano, Manuel; Biancone, Davide Maria; Capata, Giulia; Tristano, Isabella; Martucci, Vanessa; Guido, Cristiana Alessia; Anaclerio, Silvia; Loffredo, Lorenzo; Zicari, Anna Maria; Duse, Marzia; Spalice, Alberto (Frontiers in Pediatrics, 2019)
Objective: Cardiac involvement in PANS has not been clarified relying on the scientific literature available until today. It is known that streptococcal infections play a role in the etiology of a great number of diseases including Sydenham chorea and rheumatic fever, among others. Based on the suspected pathogenesis of PANDAS (Paediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcal infections) reported in the medical literature, we decided to investigate the cardiologic involvement in children with a recent PANS/PANDAS diagnosis. Methods: The study population satisfies PANS (Swedo et al. 2012) and PANDAS (Swedo et al. 1998) criteria of diagnoses. Cardiologic assessment was performed through clinical examination, electrocardiography and echocardiography. Results: In the selected pediatric population a significant number of children presented mitral valve involvement, systolic murmurs and electrocardiographic abnormalities. High ASLOT levels not seem to be associated to a cardiac involvement. Conclusions: Often PANS is difficult to diagnose because it is little known by physicians and most of the cardiologic findings described in this study are common among the healthy pediatric population. Also ASLOT levels seems not to be predictive of cardiac involvement. Furthermore the existence of PANDAS as clinical entity associated with a group of anti-neuronal autoantibodies found in Sydenham chorea is still controversial. We recommend a complete cardiologic evaluation in those children who meet the PANS/PANDAS diagnostic criteria.